Antiretroviral Long-Term Efficacy and Resistance of Lopinavir/Ritonavir Plus Lamivudine in HIV-1-Infected Treatment-Naïve Patients (ALTERLL): 144-Week Results of a Randomized, Open-Label, Non-Inferiority Study From Guangdong, China - Guo, Peng-Le; He, Hao-Lan; Chen, Xie-Jie; Chen, Jin-Feng; Chen, Xiao-Ting; Lan, Yun; Wang, Jian; Du, Pei-Shan; Zhong, Huo-Lin; Li, Hong; Liu, Cong; Li, Li-Ya; et al. (Frontiers in Pharmacology, 2021)
Dual therapy with lopinavir/ritonavir (LPV/r) plus lamivudine (3TC) has been demonstrated to be non-inferior to the triple drug regimen including LPV/r plus two nucleoside reverse transcriptase inhibitors (NRTIs) in 48-week studies. However, little is known about the long-term efficacy and drug resistance of this simplified strategy. A randomized, controlled, open-label, non-inferiority trial (ALTERLL) was conducted to assess the efficacy, drug resistance, and safety of dual therapy with LPV/r plus 3TC (DT group), compared with the first-line triple-therapy regimen containing tenofovir (TDF), 3TC plus efavirenz (EFV) (TT group) in antiretroviral therapy (ART)-naïve HIV-1–infected adults in Guangdong, China. The primary endpoint was the proportion of patients with plasma HIV-1 RNA < 50 copies/ml at week 144. Between March 1 and December 31, 2015, a total of 196 patients (from 274 patients screened) were included and randomly assigned to either the DT group (n = 99) or the TT group (n = 97). In the primary intention-to-treat (ITT) analysis at week 144, 95 patients (96%) in the DT group and 93 patients (95.9%) in the TT group achieved virological inhibition with plasma HIV-1 RNA <50 copies/ml (difference: 0.1%; 95% CI, –4.6–4.7%), meeting the criteria for non-inferiority. The DT group did not show significant differences in the mean increase in CD4+ cell count (247.0 vs. 204.5 cells/mm3; p = 0.074) or the CD4/CD8 ratio (0.47 vs. 0.49; p = 0.947) from baseline, or the inflammatory biomarker levels through week 144 compared with the TT group. For the subgroup analysis, baseline high viremia (HIV-1 RNA > 100,000 copies/ml) and genotype BC did not affect the primary endpoint or the mean increase in CD4+ cell count or CD4/CD8 ratio from baseline at week 144. However, in patients with genotype AE, the DT group showed a higher mean increase in CD4+ cell count from baseline through 144 weeks than the TT group (308.7 vs. 209.4 cells/mm3; p = 0.038). No secondary HIV resistance was observed in either group. Moreover, no severe adverse event (SAE) or death was observed in any group. Nonetheless, more patients in the TT group (6.1%) discontinued the assigned regimen than those in the DT group (1%) due to adverse events. Dual therapy with LPV/r plus 3TC manifests long-term non-inferior therapeutic efficacy, low drug resistance, good safety, and tolerability compared with the first-line triple-therapy regimen in Guangdong, China, indicating dual therapy is a viable alternative in resource-limited areas. Clinical Trial Registration: [http://www.chictr.org.cn], identifier [ChiCTR1900024611].